A Modular Fluorescent Probe for Viscosity and Polarity Sensing in DNA Hybrid Mesostructures. Issue 5 (23rd December 2020) - Ludwanowski, Simon; Samanta, Avik; Loescher, Sebastian; Barner‐Kowollik, Christopher; Walther, Andreas
Abstract: There exists a critical need in biomedical molecular imaging and diagnostics for molecular sensors that report on slight changes to their local microenvironment with high spatial fidelity. Herein, a modular fluorescent probe, termed StyPy, is rationally designed which features i) an enormous and tunable Stokes shift based on twisted intramolecular charge transfer (TICT) processes with no overlap, a broad emission in the far‐red/near‐infrared (NIR) region of light and extraordinary quantum yields of fluorescence, ii) a modular applicability via facile para ‐fluoro‐thiol reaction (PFTR), and iii) a polarity‐ and viscosity‐dependent emission. This renders StyPy as a particularly promising molecular sensor. Based on the thorough characterization on the molecular level, StyPy reports on the viscosity change in all‐DNA microspheres and indicates the hydrophilic and hydrophobic compartments of hybrid DNA‐based mesostructures consisting of latex beads embedded in DNA microspheres. Moreover, the enormous Stokes shift of StyPy enables one to detect multiple fluorophores, while using only a single laser line for excitation in DNA protocells. The authors anticipate that the presented results for multiplexing information are of direct importance for advanced imaging in complex soft matter and biological systems. Abstract : The rational design of StyPy enables a push–pull system that undergoes a twisted intramolecular charge transfer (TICT) in its excited state and is applied to sense local viscosities and polarities in DNA hybrid mesostructures. The enormous Stokes shift of 250 nm enables to concurrently detect StyPy and conventional dyes with a single laser excitation.